Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan FazNet Palembang - Agustina, Agustina; Cholid, Idham (MDP Student Conference, 2025)
This study examines how price, product quality, and service quality affect customer satisfaction of Wifi FazNet Palembang City. This survey involved 393 Wifi FazNet Palembang City customers. Sampling was done purposively. This partial test finding indicated that price affects customer satisfaction, product quality does not affects customer satisfaction, and service quality does affects customer satisfaction. The result of the simultaneous test finding Price, product quality, and service quality also affect consumer satisfaction